Quality of Chiffon Cake Soy Milk - Ramadhan, Anugerah; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Research aims to analyze the quality of chiffon cake using cow's milk and soy milk to find alternatives for people with cow's milk allergy. This type of research is experimental with three timem repetition. The research was conducted at the Catering Workshop, Department of Family Welfare, Faculty of Tourism and Hospitality, Padang State University in September 2021. Primary data were sourced from 5 expert panelists. The independent variable is chiffon cake with cow's milk and soy milk along the dependent variable is the quality of the chiffon cake. The data obtained were tabulated into tabular form and analyzed by T test (t test). The results showed that statistically it had no significant effect on high volume, symmetrical round shape, volume expands, color, neat round shape, scent soft texture, fine porous texture and taste. The results of the study showed that chiffon cake processed using soy milk resulted in an expanding volume (3.87), a high volume (3.40), a symmetrical round shape (3.40), (3.13), brownish yellow color (3,20), fragrant aroma (3.47), soft texture (3.87), fine-porous texture (3.80), sweet taste (3, 67). Overall X1 and X2 do not have a significant difference.